ANALISIS TATANIAGA KUBIS (Brassica oleraceae) (Studi Kasus di Desa Deles Kecamatan Bawang Kabupaten Batang) - Tri Nofianto Aji; Renan Subantoro; Eka Dewi Nurjayanti (MEDIAGRO, 2015)
Deles village is one of cabbages producers that located near with the economic central in Bawang District. The distance between Deles and Bawang which is near, has advantage for the cabbages farmer to distribute their agricultural produce. The objectives of the research are 1). To know the pattern of trading system 2). To determine the amount of profits earned by farmers in various pattern of trading system 3). To know the efficiency of cabbages trading system based on marketings margin, farmer’s share, and profit ratio. The location of research selected by purposive method, that is Deles Village, because Deles Village is the largest producer of cabbage in Bawang District. The number of farmers were selected as respondent are 30 farmers who own land, which consist of 15 farmers from Mulya Sari farmers group and 15 farmers from Subur Makmur farmers group. Sampling method of marketing agencies conducted by snowball sampling method. The research used qualitative and quantitative analysis methods. Based on the results of the research, there are three pattern of cabbage trading system in Deles Village, which are zero level, one level, and two level of cabbage  trading system. Zero level of cabbage consist of farmers → consumers, the one level consist of farmers → retailers → consumers. and two level consist of farmers → collectors → retailers → consumers. There are 5 farmers who are involved in zero level of cabbage trading system, 13 farmers who are involved in one level, and 12 farmers who are involved in two level. The biggest profits are obtained by farmers in cabbage trading system zero level, that is Rp 691,64 /kg. The most efficient cabbage is trading system two level, with a marketing margin of Rp 2.175 /kg, farmer’s share of 20,90 %, and a profit ratio Rp 2,21 /kg. Keywords: Cabbage, farmer’s share, profit ratio, trading system.